Shear fracture evolution in rocks examined using a novel shear device associated with acoustic emissions. (1st April 2019) - Chen, Li-Hsien; Chen, Wei-Chih; Chen, Yao-Chung
Highlights: A novel shear device with an opened-shear-box design was developed. Acoustic emission was used to detect the micro-cracks position. The complete load behavior was obtained using COD control technique. Shear fracture initiation and propagation of granite and sandstone was observed. Abstract: This study constructs a new shear test method composed of an open-box-style shear device with a crack-opening-displacement (COD) extensometer associated with a non-destructive acoustic emission (AE) detection system for examining the complete load behavior and the shear fracture triggering position and subsequent fracture propagation of two rock types (Charcoal granite and Berea sandstone). The complete macroscopic view loading curve presents that the pre-peak shear stiffness and shear strength of granite are higher than those for sandstone. The post-peak load behavior of both rocks trend towards the unstable fracture type (Class II), whereas in the microscopic view, the localization of AE events occurred before the peak and is located near the middle of the specimen. The AE localization spatial distribution is in good agreement with the macro-crack position. This suggests that the AE localization distribution is related to the macro-crack initiation position. After localization, the AE events then propagate following the shear direction. The results obtained in this study provide a better understanding of the shear fracture mechanism of brittle rock material.